HIGHER EDUCATION, QUALITY OF HIGHER EDUCATION, EXPERT SUPPORT AND ITS ASSURANCE: THE CANONIZATION OF CONCEPTS (THEORETICAL AND METHODOLOGICAL DISCOURSE) - Batechko, Nina (The Modern Higher Education Review, 2018)
The article highlights the peculiarities of the justification of the concept of “quality of education” in modern scientific discourse. At the same time, the investigated phenomenon is presented in the interpretation of the systemic and synergistic approaches. It is noted that the synergy of systematic and synergistic approaches can serve as a theoretical and methodological justification for the quality of education. In the context of systemic and synergetic approaches, modern realities of introducing the basic principles of the quality of education and its expert support in the national higher school are analysed. It has been proved that taking into account the best European principles for ensuring the quality of education and own vision of the solution of the problem will allow accelerating the processes of reforming the education sector in Ukraine.